TINJAUAN TERHADAP RATIO DECIDENDI HAKIM PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI SAMARINDA DALAM PERKARA PEMUTUSAN HUBUNGAN KERJA BURUH PT.SIMS JAYA KALTIM DI KABUPATEN PASER - Neneng Herawati (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Termination of Employment is a type of industrial relations dispute regulated in Act Number 13 of 2003 and Act Number 2 of 2004. Termination of Employment occurs when there are violations committed by workers in the Labor Law, Collective Labor Agreement, and Regulations Company. Or conversely there is also termination of employment done by companies against their workers. Termination of employment in this case was filed by the company on the grounds of inviting or influencing others to strike. . In the trial both based on the evidence and witnesses the reasons for the lawsuit were not proven, but even though based on the evidence and witnesses were not proven, the Panel of Judges granted the Plaintiff's claim by stating that the employment relationship between the Plaintiff and Defendant was terminated on the grounds that the employment relationship was not harmonious.This type of research used in this paper the author uses normative juridical research methods, namely